In-situ annealing of self-ion irradiation damage in tungsten. Issue 1712 (21st July 2014) - Yi, Xiaoou.; Jenkins, Michael L.; Roberts, Steve G.; Kirk, Marquis A.
ABSTRACT: In our earlier work [1] microstructural evolution in tungsten under self-ion irradiation was investigated as a function of temperature and dose by in-situ 150 keV W + ion irradiations on the IVEM-Tandem facility at Argonne National Laboratory (ANL). The present work focuses on the thermal stability of this damage. Thin foils of tungsten were irradiated at room temperature (R.T.) to fluences up to 10 18 W + m -2 (∼ 1.0 dpa) and were then annealed in-situ for up to 120 min at temperatures between 300 and 800°C. We found that: (1) loops with Burgers vectors ½ <111> and <100> coexist during annealing; (2) <100> is not a stable loop configuration above 300°C and the fraction of such loops decreased with increasing temperature and/or time; (3) changes in loop populations during annealing were very sensitive to temperature, but less sensitive to time. The majority of changes occurred within 15 min, and were associated with the loss of small (1-2 nm) dislocation loops. The origin of these trends is discussed by considering defect mobility and the energetics of defect configurations predicted by previous DFT calculations [2].